2020
DOI: 10.3390/biomedicines8090363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subclinical Congestion on Outcome of Patients Undergoing Mitral Valve Surgery

Abstract: Since risk assessment prior to cardiac surgery is based on proven but partly unsatisfactory scores, the need for novel tools in preoperative risk assessment taking into account cardiac decompensation is obvious. Even subclinical chronic heart failure is accompanied by an increase in plasma volume. This increase is illustrated by means of a plasma volume score (PVS), calculated using weight, gender and hematocrit. A retrospective analysis of 187 consecutive patients with impaired left ventricular function under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a retrospective cohort study including 1,887 patients undergoing coronary artery bypass graft surgery, preoperative assessment of Hakimderived ePVS ≥5.6% was associated with worse prognosis in a post-operative period 54 . Similarly, worse prognostic value of higher ePVS was reported in patients undergoing transaortic valvular intervention or mitral valvular intervention 55,56 . In addition, in 1,369 acute dyspneic patients admitted to the emergency department, the highest tertiles of admission Duarte-derived ePVS was associated with AHF diagnosis (adjusted OR [95%CI]=1.64 [1.16-2.33], p=0.005) as the main cause of dyspnea.…”
Section: Non-heart Failurementioning
confidence: 90%
“…In a retrospective cohort study including 1,887 patients undergoing coronary artery bypass graft surgery, preoperative assessment of Hakimderived ePVS ≥5.6% was associated with worse prognosis in a post-operative period 54 . Similarly, worse prognostic value of higher ePVS was reported in patients undergoing transaortic valvular intervention or mitral valvular intervention 55,56 . In addition, in 1,369 acute dyspneic patients admitted to the emergency department, the highest tertiles of admission Duarte-derived ePVS was associated with AHF diagnosis (adjusted OR [95%CI]=1.64 [1.16-2.33], p=0.005) as the main cause of dyspnea.…”
Section: Non-heart Failurementioning
confidence: 90%
“…The association of PVS with outcomes following TAVR was also demonstrated by Seoudy et al (33). A study by Schaefer et al examined the association between PVS and mortality following mitral valve surgery (34).…”
Section: Introductionmentioning
confidence: 73%
“…Seoudy et al identified an ePVS cut-off of −5.4 as a significant predictor of these outcomes in a TAVI cohort at 1 year after the intervention (33). Interestingly, Schaefer et al identified a higher ePVS cut-off of 3.1 when analyzing the correlation of the calculated plasma volume status with shortand long-term outcomes in patients undergoing mitral valve surgery (34). In summary, the ePVS cut-off identified by our study is in agreement with data from other trials in different patient collectives and thus provides initial proof that, on the one hand, ePVS might represent a viable stratification parameter for patients undergoing isolated tricuspid valve surgery, and on the other hand, ePVS might represent an overarching heart failurerelated stratification parameter that might play a key role in identifying at-risk cardiac surgery patients undergoing a number of different interventions.…”
Section: Discussionmentioning
confidence: 99%